Prosper or beggar thy neighbour: Industrial policy effect of free trade zones. - Jane Du; Cheng King; Xinxiang Shi (PLoS ONE, 2023)
Firms that stand to gain from the institutional framework of a free trade zone (FTZ) usually opt for locations in the FTZ region where they could expect higher returns on investment. This concentration of industries in FTZs can result in a reallocation of productivity, potentially leading to the "hollowing out" effect in existing industries, which can have a beggar-thy-neighbour effect on regional growth. Over the long term, the outcome, whether it leads to prosperity or detriment, hinges on the delicate balance between the immediate static loss associated with resource reallocation and the dynamic gains based on traditional manufacturing sector's growth along the evolving FTZ environment.